Answer:
The awnser for that is -2, my friend
Harry gave away 3/6, or half of the brownies
1/6 plus 2/6 equals 3/6
Answer:
see explanation
Step-by-step explanation:
Given
4
- 5a² + 1 = 0
Use the substitution u = a², then equation is
4u² - 5u + 1 = 0
Consider the product of the coefficient of the u² term and the constant term
product = 4 × 1 = 4 and sum = - 5
The factors are - 4 and - 1
Use these factors to split the u- term
4u² - 4u - u + 1 = 0 ( factor the first/second and third/fourth terms )
4u(u - 1) - 1(u - 1) = 0 ← factor out (u - 1) from each term
(u - 1)(4u - 1) = 0
Equate each factor to zero and solve for u
u - 1 = 0 ⇒ u = 1
4u - 1 = 0 ⇒ 4u = 1 ⇒ u = 
Convert u back into terms of a, that is
a² = 1 ⇒ a = ± 1
a² =
⇒ a = ± 
Solutions are a = ± 1 , a = ± 
Try and get the variable by its self by -81 from both sides then divide it by 7 and get ur answer.
The total annual returns on each of the following investments would be 65 times 11,300 and the answer you’ll get divide by 2